2017
DOI: 10.3390/w9060422
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Glaciological and Hydrological Trends in the Pamir Mountains, Central Asia

Abstract: With respect to meteorological changes and glacier evolution,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The current patterns of ruggedness in the landscape corroborated with the present DEM, and suggested that ibex distribution from Lahaul, India, to Tajikistan (geo-points #1 to 6) were sustained with enormous undulation and substantial increase in the contours than relatively less heterogeneity in the landscape from Tajikistan to Kazakhstan (geo-points from #6 to 8) during the Pleistocene Transitions ( Figure 3 ; ruggedness graph). Further, the annual mean temperature and precipitation, which are the major contributors of the climatic envelope supported by the mountains that lie in the south of the Pamir range to the border of Hindu Kush Mountains along Afghanistan’s Wakhan Corridor, have been warmer than the north of the Pamir range as they connect to Tian Shan mountains along the Alay Valley of Kyrgyzstan [ 69 ]. Since the annual temperature and precipitation regulate vegetation growth [ 48 , 49 , 63 ], we believe that after the geographical split of Himalayan ibex into glacial refugium during the Middle Pleistocene Transitions, this population would have experienced relatively more conducive ecological conditions than its counterparts in the north of the Pamir range.…”
Section: Discussionmentioning
confidence: 99%
“…The current patterns of ruggedness in the landscape corroborated with the present DEM, and suggested that ibex distribution from Lahaul, India, to Tajikistan (geo-points #1 to 6) were sustained with enormous undulation and substantial increase in the contours than relatively less heterogeneity in the landscape from Tajikistan to Kazakhstan (geo-points from #6 to 8) during the Pleistocene Transitions ( Figure 3 ; ruggedness graph). Further, the annual mean temperature and precipitation, which are the major contributors of the climatic envelope supported by the mountains that lie in the south of the Pamir range to the border of Hindu Kush Mountains along Afghanistan’s Wakhan Corridor, have been warmer than the north of the Pamir range as they connect to Tian Shan mountains along the Alay Valley of Kyrgyzstan [ 69 ]. Since the annual temperature and precipitation regulate vegetation growth [ 48 , 49 , 63 ], we believe that after the geographical split of Himalayan ibex into glacial refugium during the Middle Pleistocene Transitions, this population would have experienced relatively more conducive ecological conditions than its counterparts in the north of the Pamir range.…”
Section: Discussionmentioning
confidence: 99%
“…The highest rates of climate change were recorded in Uzbekistan between 1950 and 2005 at rate of 0.29 °C and in Kazakhstan at 0.26 °C per decade [6]. In addition, the climate change rate in Kirgizstan (1883-2005) and Tajikistan were 0.08 °C and 0.10 °C per decade, respectively [7]. In Kirgizstan and Tajikistan the area of forests and mountain ranges is comparatively more and the possible negative impact of climatic factors is relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Mass balances of the glaciers located in the eastern part of Western Pamir can respond to the north-to-south gradient (summer cooling for northern Pamir and warming trend for southern Pamir) reported by Knoche et al (2017). These mass balances are therefore mainly driven by air temperatures (Fig.…”
Section: Analysis I: Har Dataset and Mb Barandunetalmentioning
confidence: 93%